Tracing and attribution of V-type nerve agents in human exposure by strategy of assessing the phosphonylated and disulfide adducts on ceruloplasmin. (30th January 2020) - Fu, Feiyan; Chen, Jialin; Zhao, Pengcheng; Lu, Xiaogang; Gao, Runli; Chen, Dong; Liu, Haibo; Wang, Hongmei; Pei, Chengxin
Abstract: V-type agents are highly toxic organophosphorus nerve agents that inhibit acetylcholinesterase in the nervous system, causing a series of poison symptoms. Trace analytical methods are essential for the specific verification of exposure to these agents, especially for human exposure. This paper investigates the phosphonylated and disulfide adducts between human ceruloplasmin and O-ethyl S-(2-(diisopropylamino)ethyl) methylphosphonothioate (VX), O -isobutyl S -(2-(diethylamino)ethyl) methylphosphonothioate (VR), and O -butyl S -(2-(diethylamino)ethyl) methylphosphonothioate (Vs). After being digested by trypsin, the mixture of peptides was separated by a nano-liquid chromatography (nano-LC) and analyzed using quadrupole-orbitrap mass spectrometry (Q-Orbitrap-MS). The sensitive LC-MS/MS-assisted proteomics approach was developed to achieve the identification of human exposure to V-type agents based on these modified sites; results revealed that potential biomarkers could be derived from adducts based on the sulfur- and phosphorus-containing groups of V-type agents. This work offered a novel insight into the mechanism of disulfide-containing adducts resulting from the replacement of disulfide bridges by the thiolate groups from the V-type agents. Moreover, four disulfide adducts on human ceruloplasmin were also discovered during this research, specifically confirming exposure to the V-type agents. Furthermore, molecular simulation testified to the reactivity of the modified sites. Collectively, our findings suggest that the eleven binding sites on human ceruloplasmin have the potential use as a selective marker for prediction the V-type agent exposure in humans.